2D Higher‐Metal Nitride Nanosheets for Solar Steam Generation. Issue 28 (13th June 2022) - Wang, Lifeng; Shang, Jing; Yang, Guoliang; Ma, Yuxi; Kou, Liangzhi; Liu, Dan; Yin, Huaying; Hegh, Dylan; Razal, Joselito; Lei, Weiwei
Abstract: Higher‐metal (HM) nitrides are a fascinating family of materials being increasingly researched due to their unique physical and chemical properties. However, few focus on investigating their application in a solar steam generation because the controllable and large‐scale synthesis of these materials remains a significant challenge. Herein, it is reported that higher‐metal molybdenum nitride nanosheets (HM‐Mo5 N6 ) can be produced at the gram‐scale using amine‐functionalized MoS2 as precursor. The first‐principles calculation confirms amine‐functionalized MoS2 nanosheet effectively lengthens the bonds of MoS leading to a lower bond binding energy, promoting the formation of MoN bonds and production of HM‐Mo5 N6 . Using this strategy, other HM nitride nanosheets, such as W2 N3, Ta3 N5, and Nb4 N5, can also be synthesized. Specifically, under one simulated sunlight irradiation (1 kW m ‐2 ), the HM‐Mo5 N6 nanosheets are heated to 80 °C within only ≈24 s (0.4 min), which is around 78 s faster than the MoS2 samples (102 s/1.7 min). More importantly, HM‐Mo5 N6 nanosheets exhibit excellent solar evaporation rate (2.48 kg m ‐2 h ‐1 ) and efficiency (114.6%), which are 1.5 times higher than the solar devices of MoS2 /MF. Abstract : A feasible and general method that allows the controllable synthesis of higher‐metal nitride nanosheets using amine‐functionalized transition metal dichalcogenides (TMDs) nanosheets as precursors is reported. The solar water generation devices of higher‐metal nitrides exhibit high‐efficiency water evaporation. This study provides a series of advanced higher‐metal nitrides with high‐performance photothermal conversion efficiency for solar‐driven steam evaporation.